IDENTIFICAÇÃO DA FRAGILIDADE AMBIENTAL DA BACIA HIDROGRÁFICA DO ARROIO UVARANAL, COMO SUBSÍDIO À EXPANSÃO URBANA DE TELÊMACO BORBA – PR - Bahr, Gustavo Conceição (2011)
The environmental researches which use the physical characteristics as parameter of analysis, aim at finding ways to evaluate this society changing on the nature. An appropriate spatial side view for this analysis, which has this information in an integrated method, is the hydrographic basin. For this research to be developed, it was used a methodology that identify an environmental fragility and use as parameter information about the soil‟s characteristics and declivity to determine environmental potential fragility. With the mixing of this information and the soil usage and occupation, was determined the emergent fragility of its area. A spatial side chosen for this research was Arroio Uvaranal, located in Telêmaco Borba town, PR, due the fact this basin be target of urban sprawl project where will happen significant changes in the local. To identify the environmental fragility it was used geoprocessing techniques, using satellites image and digital maps to elaborate theme chart. The results show that the most relevant potential fragility of Uvaranal Hydrographic Basin is represented by very weak classes, covering 52,84% of its area and it‟s the reason of the basin show especially low declivity associated with Latossolo Vermelho, a soil characterized by high deep and great drainage. Concerning to the emergent fragility, the most significant values are also about low and medium classes, occupying 56,87% of the Uvaranal Basin, on account of potential fragility, in addition to the land usage which gives it some protection. Therefore, it is recommended the use of work like subsides to future research considering to soil usage of Uvaranal Hydrographic Basin sprawl urban.